Racial Discrimination and Health-Related Quality of Life: An Examination Among Asian American Immigrants - Jung, Mary Y. (J Racial Ethn Health Disparities, 2021)
OBJECTIVES: We aimed to examine the relationship between everyday and major racial discrimination with health-related quality of life (HRQOL), which consists of self-rated health, days of poor physical health, mental health, and activity limitation. DESIGN: In a cross-sectional analytic sample of 524 foreign-born Asian adults, aged 18 years and older, we conducted multivariable logistic regression and multivariable negative binomial regression to examine associations between discrimination and HRQOL. Furthermore, potential effect modification was tested by gender, ethnicity, and social support. RESULTS: Associations were found between everyday racial discrimination and days of poor physical health (incidence rate ratio, IRR = 1.05), mental health (IRR = 1.03), and activity limitation (IRR = 1.05). Stronger significant associations were observed between major racial discrimination and days of poor physical health (IRR = 1.21), mental health (IRR = 1.16), and activity limitation (IRR = 1.53), adjusting for all covariates. Racial discrimination was not associated with poor self-rated health. In addition, gender significantly modified the relationship between continuous racial discrimination and activity limitation days with associations of greater magnitude among men, while social support significantly modified the association between categorized major racial discrimination and physically unhealthy days. When stratified, the association was only significant among those with low social support (IRR = 3.04; 95% CI: 1.60, 5.79) as opposed to high social support. CONCLUSIONS: This study supports the association between racial discrimination and worse HRQOL among Asian Americans, which can inform future interventions, especially among men and those with low social support, aimed at improving the quality of life in this population. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s40615-021-01067-8.